PENGEMBANGAN MICROBLOG DENGAN PENDEKATAN STEM PADA MATERI KIMIA HIJAU BERBANTUAN INSTAGRAM BERORIENTASI KEMAMPUAN LITERASI DIGITAL - Ika Rahmadhani; Naswir; Haryanto; Afrida; Asmiyunda (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Problems in chemistry learning in secondary schools include low student interest in chemistry learning, low digital literacy skills, and a lack of variety and innovation in learning media that utilize technology familiar to students. In addition, the application of the STEM approach to green chemistry material is still not optimal, so students have difficulty relating green chemistry concepts to environmental issues in everyday life. This study aims to develop Microblog learning media with an Instagram-assisted STEM approach on green chemistry material oriented towards digital literacy skills, as well as to analyze the feasibility of the product and student responses to the developed media. This research is a development study (Research and Development) using the Lee & Owens model, which includes the stages of analysis, design, development, implementation, and evaluation. The research subjects were students in class X Phase E7 at SMAN 1 Muaro Jambi. Data collection instruments included interviews, expert validation questionnaires on materials and media, teacher assessment questionnaires, and student response questionnaires. Data were analyzed descriptively, quantitatively, and qualitatively. The results of the study indicate that Microblog learning media with an Instagram-assisted STEM approach is feasible for use based on expert results and teacher assessments. The results of the student response questionnaire in the small group trial showed a percentage of more than 86.06% in the excellent category, indicating that Microblog media can increase student interest in learning, facilitate understanding of green chemistry material, and support the development of student digital literacy. Based on these research results, it can be concluded that Microblog learning media with an Instagram-assisted STEM approach to green chemistry material is feasible for use as a learning support medium and has the potential to create more interactive, contextual chemistry learning that is tailored to student characteristics.